2006
DOI: 10.1080/14417040600970614
|View full text |Cite
|
Sign up to set email alerts
|

Word processing at 19 months and its relation to language performance at 30 months: A retrospective analysis of data from German learning children

Abstract: Word processing at 19 months and its relation to language performance at 30 months: A retrospective analysis of data from German learning children U n i v e r s i t ä t P o t s d a m Abstract Recent research has shown that the early lexical representations children establish in their second year of life already seem to be phonologically detailed enough to allow differentiation from very similar forms. In contrast to these findings children with specific language impairment show problems in discriminating phono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…To summarize, our findings add to the growing body of research that shows that measures of processing linguistic information obtained early in life correlates with later language development (Bernhardt, Kemp, & Werker, ; Fernald, Perfors, & Marchman, ; Höhle, van de Vijver, & Weissenborn, ). An early assessment of prosodic skills—which is one of the earliest perceptual abilities that can be tested in infants—may indicate children at risk for developing a language‐related impairment.…”
Section: Discussionsupporting
confidence: 64%
“…To summarize, our findings add to the growing body of research that shows that measures of processing linguistic information obtained early in life correlates with later language development (Bernhardt, Kemp, & Werker, ; Fernald, Perfors, & Marchman, ; Höhle, van de Vijver, & Weissenborn, ). An early assessment of prosodic skills—which is one of the earliest perceptual abilities that can be tested in infants—may indicate children at risk for developing a language‐related impairment.…”
Section: Discussionsupporting
confidence: 64%
“…In a second study from the GLAD project, Hö hle et al (2006) investigated the relationship between word processing at 19 months using the intermodal preferential looking paradigm and language performance at 30 months using a standardised test assessing comprehension and production (SETK2). This study included seventy one children from the GLAD study.…”
Section: The Relation Between Language Acquisition and Language Procementioning
confidence: 99%
“…Two different measures of RAP ability at the early ages combined to predict about 38% of the variance in expressive LA at 16 months and were better predictors of language outcome than risk status. Among TD infants studies have found significant correlations between speech perception skills at 6 months and measures of language development collected across the second year of life, and toddlers with low language scores at 30 months showed atypical looking patterns to pictures paired with phonologically deviant (mispronounced) targets at 19 months [Tsao et al, ; Höhle et al, ]. Together, this body of work suggests that early auditory processing plays an important role in the acquisition of language: infants who have more difficulty with auditory processing show delayed language development, and infants at risk for SLI are more likely to demonstrate such difficulties.…”
Section: Early Behavioral Precursors and Developmental Patternsmentioning
confidence: 99%